Secured Voting System with Multimodal Biometric Technique using ANN - Deora, Payal; Kumar, Abhishek; M, Gayathri.; C, Malathy (International Journal of Engineering and Technology, 2018)
Free and fair elections play a major role to explicate a democratic government, but all too frequently, the actual mechanics of election has always been taken for granted in our country, the largest democracy in the world. The issue of security is very prominent in any system such as the current electoral voting system. There is no proper record of people who have already casted their vote. The voter Id card does not have any record of biometrics of the voter, so we cannot guarantee genuine voting hence creating chances of bogus voting. Therefore, we intend to aid in security of voting system by bringing advanced technologies of neural networks with multimodal biometrics (face recognition, fingerprint scan, retina scan etc). As these biometrics of a person is already recorded in their Aadhar card, so it can be used as database. At the time of voting, biometric information of a voter will be gathered and will be matched to the database obtained by Aadhar card so that the person can be identified correctly. The proposed new voting system with multimodal biometrics can help any democratic government in conducting smooth election by removing all the ambiguities and security issues of current scenario. â€˜Â